The Global Third Nuclear Age - Futter, Andrew; Castelli, Ludovica; Hunter, Cameron; Samuel, Olamide; Silvestri, Francesca; Zala, Benjamin (Taylor & Francis, 2025)
This book provides an in-depth examination of the technological, geopolitical and normative pressures driving the world into a new, more complex and potentially more dangerous Third Nuclear Age.